2016
DOI: 10.3329/bsmmuj.v9i4.29993
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance in glucose metabolism in patients with lichen planus

Abstract: Lichen planus is an inflammatory keratotic dermatosis of unknown etiology, occurs in 0.5-1.9% of the population. 1-2 Its classical clinical presentation is characterized by flat-topped, polygonal, papules or plaques of violet color. It affects primarily the flexure surface of the wrists, thighs, distal third of lower extremities, abdomen, genitals, nails and oral mucosa. Lichen planus is a pruritic, inflammatory disease of the skin, mucous membrane and hair follicles. It occurs throughout the world in all race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Although the exact aetiology is unknown, OLP often considered as a hypersensitivity reaction. Strong association with emotional stress, antihypertensive drugs, NSAIDs, infectious disease, and Glucose metabolism disturbances reported as associated risk factors for OLP 43 . Different clinical forms of OLP are detected, such as, reticular, erosive, atrophic, bullous, and plaque types.…”
Section: Oral Lichen Planusmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the exact aetiology is unknown, OLP often considered as a hypersensitivity reaction. Strong association with emotional stress, antihypertensive drugs, NSAIDs, infectious disease, and Glucose metabolism disturbances reported as associated risk factors for OLP 43 . Different clinical forms of OLP are detected, such as, reticular, erosive, atrophic, bullous, and plaque types.…”
Section: Oral Lichen Planusmentioning
confidence: 95%
“…This is a T-cell mediated autoimmune disease, in which the cytotoxic CD8+ cells lead to the apoptosis of the basal cells of the oral epithelium. The OLP is common in all cultures around the world, and comprises more than 0.5% of all dermatological visits 43 . Although the exact aetiology is unknown, OLP often considered as a hypersensitivity reaction.…”
Section: Oral Lichen Planusmentioning
confidence: 99%
“…6 It is thought that insulin-like growth factor receptors (IGF-1 Rs) are found in keratinocytes in aetiopathogenesis and that the increase in insulin in the blood affects these receptors. 7 AN is a dermatological clue to hyperinsulinaemia and has been linked with metabolic syndrome. 8 Acrochordons are small, soft, benign cutaneous tumours and these lesions appear in fold areas.…”
mentioning
confidence: 99%
“…found an average of 24.2 kg/m 2 , and Eshkevari et al22 found an average of 27.5 kg/ m 2 . Zakaria et al7 have found that patients with lichen planus have a strong risk of glucose metabolism disturbance, especially diabetes mellitus. Research results on the relationship between DM and LP are in conflict.…”
mentioning
confidence: 99%